Chitosan imprinted cross-linked material for selective adsorption of heavy metals in water, preparation method and application thereof

Through the use of sol-gel method and sodium tripolyphosphate crosslinking agent, the problem of unstable chitosan materials under acidic conditions and toxicity of traditional crosslinking agents is solved, and the high selectivity of chitosan blotting crosslinking materials is achieved. Adsorption and detoxification demonstrate the safety and efficiency of the material.

CN117339577BActive Publication Date: 2024-12-31XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311565647.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-22
Publication Date
2024-12-31
Estimated Expiration
2043-11-22

AI Technical Summary

Technical Problem

In the prior art, chitosan materials are unstable under acidic conditions, and traditional covalent crosslinking agents are toxic and harmful, resulting in the preparation process of chitosan imprinted crosslinking materials that are complex and unenvironmentally friendly, making it difficult to achieve high selectivity for heavy metals. Adsorption.

Method used

The sol-gel method is used to bind chitosan with template ions, and the environmentally friendly sodium tripolyphosphate is used as a crosslinking agent to optimize the treatment of eluent and nitric acid to form chitosan ions with specific recognition sites. Imprint crosslinked materials to achieve selective adsorption and detoxification of heavy metals in water.

Benefits of technology

It achieves high selective adsorption and detoxification of heavy metals in water, and is safe, environmentally friendly, cheap and easy to obtain, and has excellent adsorption performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117339577B_ABST
    Figure CN117339577B_ABST
Patent Text Reader

Abstract

A chitosan imprinted cross-linked material for selective adsorption of heavy metals in water. The chitosan imprinted cross-linked material has the structural formula: #imgabs0# wherein m / (m+n)≥95%. The preparation method comprises the following steps: preparing heavy metal imprinted chitosan sol, preparing heavy metal imprinted chitosan cross-linked gel balls, and eluting heavy metal imprinted chitosan cross-linked gel ball template ions. The present invention can selectively perform in-situ reduction adsorption on some heavy metals in water, and at the same time, the elution technology is carefully optimized, and the material has the characteristics of high selectivity, good adsorption performance, ability to adsorb and detoxify, low cost, easy availability, simple preparation, and environmental friendliness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of imprinted materials, and in particular to a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water bodies, a preparation method and application thereof. Background Art

[0002] With the development of human industrial activities, a large amount of heavy metals are discharged into water bodies, causing serious pollution. Heavy metal pollutants are of various types, highly toxic, difficult to completely self-purify in nature, and difficult to treat. They can migrate along rivers and spread to downstream water bodies and soil environments, causing serious impacts on the survival of animals and plants, and even enriched in the human body through the food chain, threatening human health.

[0003] The main methods for treating heavy metal wastewater that have been developed include coagulation / flocculation, ion exchange, electrodialysis, reverse osmosis, membrane separation, photocatalysis, adsorption, etc. Among them, the adsorption method has the advantages of high cost-effectiveness, environmental friendliness, wide application, and simple operation. It is the preferred method for treating heavy metal-containing wastewater. The selection of adsorption materials is the core of the adsorption method. Chitosan is a natural biomacromolecule polymer with active functional groups such as amino and hydroxyl groups. It has the advantages of high abundance, non-toxicity, good biocompatibility, good biodegradability, good macromolecular structure, multiple adsorption groups, multiple functional groups, strong selectivity, strong adsorption capacity and reducibility. It is widely used in the treatment of heavy metal-containing wastewater. However, chitosan materials are not stable under acidic conditions, so cross-linking is necessary. In addition, there are various complex components in the actual environment, and it is necessary to improve the selectivity of the material for heavy metals to ensure the smooth progress of the adsorption process. Ion imprinted materials with specific recognition functions can well meet this demand. Ion imprinting technology usually first binds the template ion to the functional matrix material, and then cross-links the template ion with a cross-linking agent. Ion-imprinted materials have a stable cavity that matches the size, charge and spatial structure of the template ions, achieving specific recognition and selective adsorption of the template ions.

[0004] At present, some researchers have used traditional covalent crosslinkers to synthesize chitosan imprinted crosslinked materials for adsorbing heavy metals. The patent application with publication number CN116731273A discloses a method for preparing Cr(III) ion imprinted materials, wherein chitosan and glutaraldehyde react to obtain Schiff base; Schiff base and 2,4-diamino-6-methyl-1,3,5-triazine are added to acetic acid to react to obtain functional monomers; then the functional monomers are added to CrCl3 solution for reaction, and then epichlorohydrin is added for crosslinking, and finally Cr(III) is eluted to obtain Cr(III) ion imprinted materials. The obtained Cr(III) imprinted materials have good selective adsorption properties, but there are still problems such as complex material preparation process, cumbersome procedures, and repeated use of toxic and harmful reagents, which are not conducive to the promotion and use of materials. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide an imprinted material for highly selective enrichment of heavy metal chromium in water bodies, a preparation method and an application thereof. After the natural macromolecular material chitosan is combined with the template ions by mixing and stirring, the environmentally friendly cross-linking agent sodium tripolyphosphate is incorporated into the main structure by a sol-gel method to form gel balls, and finally the mixed gel balls are eluted with an eluent and nitric acid to obtain a chitosan ion imprinted cross-linked material with specific recognition sites, which can selectively reduce and adsorb some heavy metals in water in situ. At the same time, the elution technology is carefully optimized, and the material has the characteristics of high selectivity, good adsorption performance, ability to adsorb and detoxify, low cost, easy availability, simple preparation and environmental friendliness.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A chitosan imprinted cross-linked material for selective adsorption of heavy metals in water, wherein the chitosan imprinted cross-linked material has the structural formula:

[0008] Among them, m / (m+n)≥95%.

[0009] The raw materials of the chitosan imprinted cross-linking material include a main material, a cross-linking agent, a template ion, and an eluent; by mass ratio, the main material: the cross-linking agent: the template ion: the eluent = (1.00-2.00): (250.53-501.05): (10.04-20.08): (1170.29-2340.58).

[0010] The main material is chitosan sol, which includes chitosan powder and glacial acetic acid solution. According to the mass ratio, chitosan powder: glacial acetic acid solution = (1.00-2.00): (50.17-100.34); the mass percentage concentration of the glacial acetic acid solution is 1.58-3.05%.

[0011] The cross-linking agent is a sodium tripolyphosphate solution; the mass percentage concentration of the sodium tripolyphosphate solution is 0.50-1.00%;

[0012] The template ion is one of Cr, Ca, Mg, Ti, Mo, W, Mn, Fe, Co, Ni, Pd, Pt, Pb, Cu, Ag, Zn, Cd, As, Hg, Ni or Al.

[0013] The eluent is one of sodium hydroxide solution, hydrochloric acid, EDTA solution or sodium chloride solution; the mass percentage concentration of the sodium hydroxide solution is 3.67-7.34%, the mass percentage concentration of the hydrochloric acid is 0.24-0.48%, the mass percentage concentration of the EDTA solution is 1.79-3.57%, and the mass percentage concentration of the sodium chloride solution is 2.64-5.27%.

[0014] When the eluent is sodium hydroxide solution, the raw material of the chitosan imprinted cross-linking material also includes an eluent neutralizer, and the eluent neutralizer is a nitric acid solution; by mass ratio, eluent: eluent neutralizer = (1170.29-2340.58): (179.80-359.60), and the mass percentage concentration of the nitric acid solution is 0.019-0.043%.

[0015] A method for preparing a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water comprises the following steps:

[0016] Step 1, preparing heavy metal imprinted chitosan sol: adding chitosan powder to a diluted glacial acetic acid solution at room temperature to obtain a mixed sol, adding template ions to the mixed sol, and mixing them evenly to obtain a heavy metal imprinted chitosan sol; in terms of mass ratio, chitosan powder: glacial acetic acid solution: template ions = (1.00-2.00): (50.17-100.34): (10.04-20.08);

[0017] Step 2, preparing heavy metal imprinted chitosan cross-linked gel spheres: under room temperature, dripping the heavy metal imprinted chitosan sol prepared in step 1 into the sodium tripolyphosphate solution drop by drop at a uniform speed to form heavy metal imprinted chitosan cross-linked gel spheres of uniform size; by mass ratio, heavy metal imprinted chitosan sol: sodium tripolyphosphate solution = (1.00-2.00): (250.53-501.05);

[0018] Step 3, heavy metal imprinted chitosan cross-linked gel ball template ion elution: add the heavy metal imprinted chitosan cross-linked gel ball prepared in step 2 into the eluent and shake, then separate the heavy metal imprinted chitosan cross-linked gel ball, add the eluent for centrifugation, and then dry under freezing conditions or at 25°C-60°C to obtain a chitosan imprinted cross-linked material for heavy metal selective adsorption; by mass ratio, heavy metal imprinted chitosan cross-linked gel ball: eluent = (1.00-2.00): (1170.29-2340.58).

[0019] When the eluent in step 3 is a sodium hydroxide solution, the heavy metal imprinted chitosan cross-linked gel balls are centrifuged in the eluent, and then the heavy metal imprinted chitosan cross-linked gel balls are placed in an eluent neutralizer for centrifugation, and the eluent neutralizer is a nitric acid solution; by mass ratio, eluent: eluent neutralizer = (1170.29-2340.58): (179.80-359.60).

[0020] A chitosan imprinted cross-linked material for selective adsorption of heavy metals in water bodies is prepared by any one of the above-mentioned methods for preparing a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water bodies.

[0021] The invention discloses an application of a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water bodies, and is applied to the purification of wastewater containing heavy metals.

[0022] Compared with the prior art, the beneficial effects of the present invention are:

[0023] 1. The main material chitosan used in the present invention is the second most abundant natural macromolecular biopolymer in the world. It exists in all arthropods, some invertebrates (such as squid and cuttlefish) and some microorganisms. Therefore, it is rich in sources, cheap and easy to obtain. At the same time, chitosan has a large number of adsorption active groups such as amino and hydroxyl groups. The present invention uses chitosan as a raw material and various typical heavy metals as template ions to prepare a heavy metal pollutant adsorption material with specific recognition performance. Compared with the prior art, it can achieve selective enrichment of highly toxic heavy metal pollutants at a relatively low cost, showing a higher environmental benefit.

[0024] 2. Traditional chitosan cross-linking agents (such as glutaraldehyde, epichlorohydrin, etc.) are irritating to the human respiratory tract and skin, and may even be carcinogenic. The sodium tripolyphosphate used in the present invention is basically harmless to the human body and is relatively stable in the environment. It is not only non-toxic and harmless, but also adds a small amount of phosphorus-containing groups to the chitosan structure, which improves the adsorption capacity of the material to a certain extent. Compared with the prior art, the present invention has the characteristics of being non-toxic, harmless and environmentally friendly.

[0025] 3. The present invention adopts ion imprinting technology, takes the target heavy metal as a template, combines the heavy metal with the amino group through chelation, then uses sodium tripolyphosphate for cross-linking polymerization, and finally removes the heavy metal in the structure with an elution agent, and neutralizes the remaining elution agent in the material with nitric acid, leaving certain specific recognition sites in the chitosan cross-linked material, so that it can selectively adsorb the heavy metals in the polluted water body, achieve targeted removal of heavy metals, eliminate interference from other substances in the water body, and make the adsorption active sites effectively act on the target heavy metal pollutants. Compared with the prior art, the present invention has the characteristics of strong adsorption selectivity.

[0026] 4. The triphosphate in the cross-linking agent sodium tripolyphosphate of the present invention combines with the protonated amino group in the main material chitosan by electrostatic action, so that the chitosan is cross-linked into a network structure with higher strength. Compared with the prior art, the prepared material has a large number of adsorption active groups such as amino groups and hydroxyl groups, and the material is safe and environmentally friendly.

[0027] In summary, compared with the prior art, the present invention adds template ions into chitosan sol by mixing and stirring and fully mixes them, so that the template ions are combined with the adsorption active sites of chitosan, and then the mixed sol is dropped into a cross-linking agent sodium tripolyphosphate solution by a sol-gel method to form chitosan imprinted cross-linked gel balls, and finally the template ions are eluted to obtain chitosan imprinted cross-linked materials. The obtained materials have the characteristics of simple preparation, environmental friendliness, low cost and easy availability, good adsorption performance, strong selectivity, in-situ detoxification and enrichment, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the preparation process of the present invention.

[0029] Figure 2 Schematic diagram of the preparation process of Example 1 of the present invention.

[0030] Figure 3 This is a schematic diagram of the structure of Example 1 of the present invention.

[0031] Figure 4 This is a FTIR comparison chart of Cr(VI) imprinted chitosan cross-linked materials prepared by five different drying methods in Example 1 of the present invention.

[0032] Figure 5 This is a comparison chart of the adsorption capacity of Cr(VI) imprinted chitosan cross-linked materials prepared by five different drying methods in Example 1 of the present invention.

[0033] Figure 6 This is a high-resolution XPS spectrum of Cr 2p after Cr(VI) is adsorbed on the Cr(VI)-imprinted chitosan cross-linked material prepared by freeze drying (IIP-LD) in Example 1 of the present invention.

[0034] Figure 7 This is an adsorption kinetics curve of the Cr(VI) imprinted chitosan cross-linked material prepared by freeze drying (IIP-LD) in Example 1 of the present invention.

[0035] Figure 8 This is a diagram showing the selectivity experimental results of the Cr(VI) imprinted chitosan cross-linked material prepared by freeze drying (IIP-LD) in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] Example 1

[0037] See also Figure 1 , Figure 2 and Figure 3 , a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water, characterized in that the chitosan imprinted cross-linked material has a structural formula of:

[0038] Among them, m / (m+n)≥95%.

[0039] The raw materials of the chitosan imprinting cross-linking material include chitosan sol, sodium tripolyphosphate solution, potassium dichromate solution, sodium hydroxide solution, and nitric acid solution; in terms of mass ratio, the chitosan sol: sodium tripolyphosphate solution: potassium dichromate solution: sodium hydroxide solution: nitric acid solution = 51.17: 250.53: 10.04: 1170.29: 179.80; the mass percentage concentration of the sodium tripolyphosphate solution is 0.50%, the mass percentage concentration of the potassium dichromate solution is 0.40%, the mass percentage concentration of the sodium hydroxide solution is 3.67%, and the mass percentage concentration of the nitric acid solution is 0.031%.

[0040] The chitosan sol comprises chitosan powder and glacial acetic acid solution; in terms of mass ratio, the chitosan powder: glacial acetic acid solution = 1.00: 50.17; the mass percentage concentration of the glacial acetic acid solution is 3.05%.

[0041] A method for preparing a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water comprises the following steps:

[0042] Step 1, preparing a Cr(VI) chitosan mixed sol: at room temperature, adding chitosan powder to a diluted glacial acetic acid solution to obtain a mixed sol, adding a potassium dichromate solution to the mixed sol, and mixing evenly to obtain a Cr(VI) imprinted chitosan sol; in terms of mass ratio, the chitosan powder: glacial acetic acid solution: potassium dichromate solution = 1.00:50.17:10.04; the mass percentage concentration of the glacial acetic acid solution is 3.05%, and the mass percentage concentration of the potassium dichromate solution is 0.40%;

[0043] Step 2, preparing Cr(VI) chitosan cross-linked mixed gel balls: at room temperature, using a 20.00 ml syringe, drip the Cr(VI) chitosan mixed sol prepared in step 1 into the sodium tripolyphosphate solution drop by drop at a uniform speed to form Cr(VI) chitosan cross-linked mixed gel balls of uniform size; in terms of mass ratio, Cr(VI) imprinted chitosan sol: sodium tripolyphosphate solution = 61.21: 250.53; the mass percentage concentration of the sodium tripolyphosphate solution is 0.50%;

[0044] Step 3, elution of Cr(VI) template ions: adding the Cr(VI) chitosan cross-linked mixed gel balls prepared in step 2 to a sodium hydroxide solution for oscillation, then separating the gel balls, adding a small amount of sodium hydroxide solution, oscillating for two days, and centrifuging twice in a centrifuge. After completion, placing the gel balls in a nitric acid solution and centrifuging three times to neutralize the residual sodium hydroxide, then washing with ultrapure water until neutral, and drying; in terms of mass ratio, Cr(VI) imprinted chitosan cross-linked gel balls: sodium hydroxide solution: nitric acid solution = 61.21: 1170.29: 179.80; the mass percentage concentration of the sodium hydroxide solution is 3.67%, and the mass percentage concentration of the nitric acid solution is 0.031%.

[0045] The drying operation in step 3 can be divided into five groups, namely freeze drying (IIP-LD), air drying at room temperature at 25°C (IIP-25), forced air drying at 30°C (IIP-30), forced air drying at 40°C (IIP-40), and forced air drying at 60°C (IIP-60).

[0046] A chitosan imprinted cross-linked material for selective adsorption of heavy metals in water bodies is prepared by any one of the above-mentioned methods for preparing a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water bodies.

[0047] The invention discloses an application of a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water bodies, and is applied to the purification of wastewater containing Cr(VI).

[0048] Example 2

[0049] A chitosan imprinted cross-linked material for selective adsorption of heavy metals in water, characterized in that the chitosan imprinted cross-linked material has the structural formula:

[0050] Among them, m / (m+n)≥95%.

[0051] The raw materials of the chitosan imprinting cross-linking material include chitosan sol, sodium tripolyphosphate solution, lead nitrate solution and EDTA solution; in terms of mass ratio, the chitosan sol: sodium tripolyphosphate solution: lead nitrate solution: EDTA solution = 63.96: 313.16: 12.55: 1462.86; the mass percentage concentration of the sodium tripolyphosphate solution is 0.63%, the mass percentage concentration of the lead nitrate solution is 0.40%, and the mass percentage concentration of the EDTA solution is 3.57%.

[0052] The chitosan sol comprises chitosan powder and glacial acetic acid solution; in terms of mass ratio, the chitosan powder: glacial acetic acid solution = 1.25: 62.71; the mass percentage concentration of the glacial acetic acid solution is 1.58%.

[0053] A method for preparing a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water comprises the following steps:

[0054] Step 1, preparing a Pb(II) chitosan mixed sol: at room temperature, adding chitosan powder to a diluted glacial acetic acid solution to obtain a mixed sol, adding a lead nitrate solution to the mixed sol, and mixing evenly to obtain a Pb(II) chitosan mixed sol; in terms of mass ratio, the chitosan powder: glacial acetic acid solution: lead nitrate solution = 1.25: 62.71: 12.55; the mass percentage concentration of the glacial acetic acid solution is 1.58%, and the mass percentage concentration of the lead nitrate solution is 0.40%;

[0055] Step 2, preparing Pb(II) chitosan cross-linked mixed gel spheres: at room temperature, using a syringe to drop the Pb(II) chitosan mixed sol prepared in step 1 into the sodium tripolyphosphate solution drop by drop at a uniform speed to form Pb(II) chitosan cross-linked mixed gel spheres of uniform size; in terms of mass ratio, Pb(II) chitosan mixed sol: sodium tripolyphosphate solution = 76.51:313.16; the mass percentage concentration of the sodium tripolyphosphate solution is 0.63%;

[0056] Step 3, Pb(II) template ion elution: add the Pb(II) chitosan cross-linked mixed gel balls prepared in step 2 to an EDTA solution and shake, then separate the gel balls, add a small amount of EDTA solution and centrifuge twice in a centrifuge, and after completion, place the gel balls in a nitric acid solution and centrifuge three times, and then freeze-dry; by mass ratio, Pb(II) chitosan cross-linked mixed gel balls: EDTA solution = 76.51: 1462.86; the mass percentage concentration of the EDTA solution is 3.57%.

[0057] A chitosan imprinted cross-linked material for selective adsorption of heavy metals in water bodies is prepared by any one of the above-mentioned methods for preparing a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water bodies.

[0058] The invention discloses an application of a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water bodies, and is applied to the purification of wastewater containing Pb(II).

[0059] Example 3

[0060] A chitosan imprinted cross-linked material for selective adsorption of heavy metals in water, characterized in that the chitosan imprinted cross-linked material has the structural formula:

[0061] Among them, m / (m+n)≥95%.

[0062] The raw materials of the chitosan imprinting cross-linking material include chitosan sol, sodium tripolyphosphate solution, copper acetate solution, and hydrochloric acid solution; calculated by mass ratio, the chitosan sol: sodium tripolyphosphate solution: copper acetate solution, hydrochloric acid solution = 76.76: 375.79: 15.06: 1755.44; the mass percentage concentration of the sodium tripolyphosphate solution is 0.76%, the mass percentage concentration of the copper acetate solution is 0.40%, and the mass percentage concentration of the hydrochloric acid solution is 0.36%.

[0063] The chitosan sol comprises chitosan powder and glacial acetic acid solution; in terms of mass ratio, the chitosan powder: glacial acetic acid solution = 1.5:75.26; the mass percentage concentration of the glacial acetic acid solution is 1.95%.

[0064] A method for preparing a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water comprises the following steps:

[0065] Step 1, preparing a Cu(II) chitosan mixed sol: at room temperature, adding chitosan powder to a diluted glacial acetic acid solution to obtain a mixed sol, adding a cupric acetate solution to the mixed sol, and mixing evenly to obtain a Cu(II) chitosan mixed sol; in terms of mass ratio, the chitosan powder: glacial acetic acid solution: cupric acetate solution = 1.5:75.26:15.06; the mass percentage concentration of the glacial acetic acid solution is 1.95%, and the mass percentage concentration of the cupric acetate solution is 0.40%;

[0066] Step 2, preparing Cu(II) chitosan cross-linked mixed gel spheres: at room temperature, using a syringe to drop the Cu(II) chitosan mixed sol prepared in step 1 into the sodium tripolyphosphate solution drop by drop at a uniform speed to form a Cu(II) chitosan mixed sol of uniform size; in terms of mass ratio, the Cu(II) chitosan mixed sol: sodium tripolyphosphate solution = 91.82:375.79; the mass percentage concentration of the sodium tripolyphosphate solution is 0.76%;

[0067] Step 3, Cu(II) template ion elution: add the Cu(II) chitosan cross-linked mixed gel balls prepared in step 2 into a hydrochloric acid solution and shake, then separate the gel balls, add a small amount of hydrochloric acid solution and centrifuge twice in a centrifuge, and then freeze-dry; by mass ratio, Cu(II) chitosan cross-linked mixed gel balls: hydrochloric acid solution = 91.82: 1755.44, and the mass percentage concentration of the hydrochloric acid solution is 0.36%.

[0068] A chitosan imprinted cross-linked material for selective adsorption of heavy metals in water bodies is prepared by any one of the above-mentioned methods for preparing a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water bodies.

[0069] The invention discloses an application of a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water bodies, and is applied to the purification of wastewater containing Cu(II).

[0070] Example 4

[0071] A chitosan imprinted cross-linked material for selective adsorption of heavy metals in water, characterized in that the chitosan imprinted cross-linked material has the structural formula:

[0072] Among them, m / (m+n)≥95%.

[0073] The raw materials of the chitosan imprinted cross-linking material include chitosan sol, sodium tripolyphosphate solution, manganese chloride solution, and hydrochloric acid solution; calculated by mass ratio, the chitosan sol: sodium tripolyphosphate solution: manganese chloride solution, hydrochloric acid solution = 89.55:438.42:17.57:2048.01; the mass percentage concentration of the sodium tripolyphosphate solution is 0.89%, the mass percentage concentration of the manganese chloride solution is 0.40%, and the mass percentage concentration of the hydrochloric acid solution is 0.48%.

[0074] The chitosan sol comprises chitosan powder and glacial acetic acid solution; in terms of mass ratio, the chitosan powder: glacial acetic acid solution = 1.75:87.80; the mass percentage concentration of the glacial acetic acid solution is 2.32%.

[0075] A method for preparing a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water comprises the following steps:

[0076] Step 1, preparing a Mn(II) chitosan mixed sol: at room temperature, adding chitosan powder to a diluted glacial acetic acid solution and mixing to obtain a mixed sol, adding a manganese chloride solution to the mixed sol, and mixing evenly to obtain a Mn(II) chitosan mixed sol; in terms of mass ratio, the chitosan powder: glacial acetic acid solution: manganese chloride solution = 1.75: 87.80: 17.57; the mass percentage concentration of the glacial acetic acid solution is 2.32%, and the mass percentage concentration of the manganese chloride solution is 0.40%;

[0077] Step 2, preparing Mn(II) chitosan cross-linked mixed gel spheres: at room temperature, using a syringe to drop the Mn(II) chitosan mixed sol prepared in step 1 into the sodium tripolyphosphate solution drop by drop at a uniform speed to form a Mn(II) chitosan mixed sol of uniform size; in terms of mass ratio, the Mn(II) chitosan mixed sol: sodium tripolyphosphate solution = 107.12: 438.42; the mass percentage concentration of the sodium tripolyphosphate solution is 0.89%;

[0078] Step 3, Mn(II) template ion elution: add the Mn(II) chitosan cross-linked mixed gel balls prepared in step 2 into a hydrochloric acid solution and shake, then separate the gel balls, add a small amount of hydrochloric acid solution and centrifuge twice in a centrifuge, and then freeze-dry; by mass ratio, Mn(II) chitosan cross-linked mixed gel balls: hydrochloric acid solution = 107.12: 2048.01, and the mass percentage concentration of the hydrochloric acid solution is 0.48%.

[0079] A chitosan imprinted cross-linked material for selective adsorption of heavy metals in water bodies is prepared by any one of the above-mentioned methods for preparing a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water bodies.

[0080] The invention discloses an application of a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water bodies, and is applied to the purification of wastewater containing Mn(II).

[0081] Example 5

[0082] A chitosan imprinted cross-linked material for selective adsorption of heavy metals in water, characterized in that the chitosan imprinted cross-linked material has the structural formula:

[0083] Among them, m / (m+n)≥95%.

[0084] The raw materials of the chitosan imprinting cross-linking material include chitosan sol, sodium tripolyphosphate solution, cobalt chloride solution and hydrochloric acid solution; in terms of mass ratio, the chitosan sol: sodium tripolyphosphate solution: cobalt chloride solution and hydrochloric acid solution are 102.34:501.05:20.08:2340.58; the mass percentage concentration of the sodium tripolyphosphate solution is 1.00%, the mass percentage concentration of the cobalt chloride solution is 0.40%, and the mass percentage concentration of the hydrochloric acid solution is 0.24%.

[0085] The chitosan sol comprises chitosan powder and glacial acetic acid solution; in terms of mass ratio, the chitosan powder: glacial acetic acid solution = 2.00: 100.34; the mass percentage concentration of the glacial acetic acid solution is 2.69%.

[0086] A method for preparing a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water comprises the following steps:

[0087] Step 1, preparing Co(II) chitosan mixed sol: at room temperature, adding chitosan powder to a diluted glacial acetic acid solution and mixing to obtain a mixed sol, adding a cobalt chloride solution to the mixed sol, and mixing evenly to obtain a Co(II) chitosan mixed sol; in terms of mass ratio, chitosan powder: glacial acetic acid solution: cobalt chloride solution = 2.00: 100.34: 20.08; the mass percentage concentration of the glacial acetic acid solution is 2.69%, and the mass percentage concentration of the cobalt chloride solution is 0.40%;

[0088] Step 2, preparing Co(II) chitosan cross-linked mixed gel spheres: at room temperature, using a syringe to drop the Co(II) chitosan mixed sol prepared in step 1 into the sodium tripolyphosphate solution drop by drop at a uniform speed to form a Co(II) chitosan mixed sol of uniform size; in terms of mass ratio, the Co(II) chitosan mixed sol: sodium tripolyphosphate solution = 122.42: 501.05; the mass percentage concentration of the sodium tripolyphosphate solution is 1.00%;

[0089] Step 3, Co(II) template ion elution: add the Co(II) chitosan cross-linked mixed gel balls prepared in step 2 into a hydrochloric acid solution and shake, then separate the gel balls, add a small amount of hydrochloric acid solution and centrifuge twice in a centrifuge, and then freeze-dry; by mass ratio, Co(II) chitosan cross-linked mixed gel balls: hydrochloric acid solution = 122.42: 2340.58; the mass percentage concentration of the hydrochloric acid solution is 0.24%.

[0090] A chitosan imprinted cross-linked material for selective adsorption of heavy metals in water bodies is prepared by any one of the above-mentioned methods for preparing a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water bodies.

[0091] The invention discloses an application of a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water, and is applied to the purification of wastewater containing Co(II).

[0092] See also Figure 4 , showing the FTIR spectra of different chitosan imprinted cross-linked materials prepared by five different drying methods in Example 1. The peak positions of the samples prepared by freeze drying in Example 1 are 3359.19, 2871.71, 1589.69, 1149.55, 1027.29, 892.63 cm -1 The peak positions of the samples prepared at different temperatures are similar to those of IIP, but at 3359.19, 2871.71 and 1589.69 cm -1The peak intensity at 40°C increased slightly, while the related phosphorus groups weakened slightly, proving that the cross-linking degree of samples prepared at other drying temperatures was weakened except for the samples prepared under freeze-drying conditions. This is because the electrostatic interaction between the triphosphate groups and the protonated amino groups through ionic cross-linking was weakened during the blast heating process, resulting in the cross-linking agent being unable to remain normally in the structure of the material.

[0093] See also Figure 5 In Example 1, the adsorption capacity of different samples prepared by the five different drying methods is different. Specifically, the sample prepared under freeze drying has the best adsorption performance, which can reach 95.53%, followed by the sample prepared under 40°C forced air drying, and the sample prepared under 60°C forced air drying has the worst adsorption performance. The reasons for this experimental result may be: 1) The pore characteristics of the imprinted material determine its selectivity and adsorption performance, and freeze drying can well maintain the physical structure characteristics of the imprinted material. In contrast, the samples prepared at other temperatures all show different degrees of collapse due to water evaporation; 2) High temperature will change the chemical structure of some heat-labile groups of the sample, making it unable to exert its adsorption performance.

[0094] See also Figure 6 , showing the Cr 2p high-resolution XPS spectrum of the best Cr(VI) imprinted chitosan cross-linked material (freeze-dried in Example 1) after adsorption of Cr(VI). The spectrum shows that after adsorption of Cr(VI), the Cr in the material exists in two valence states, of which Cr(III) accounts for 61.08% of the total Cr, proving that the chitosan imprinted cross-linked material reduces most of the Cr(VI) enriched in the material, greatly reducing its toxicity.

[0095] See also Figure 7 , showing the kinetic curve of the best Cr(VI) imprinted chitosan cross-linked material. After 24 hours of adsorption, the adsorption rate of the material was as high as 100%, and the residual Cr(VI) in the solution was below the detection limit, indicating that the material has good adsorption performance for Cr(VI).

[0096] See also Figure 8 The best Cr(VI) imprinted chitosan cross-linked material (freeze-dried in Example 1) has good selectivity for Cr(VI). + , K + Mg 2+ , Ca 2+ 、NO3 - , Cl - 、HCO3 - 、SO4 2-), low molecular weight organic acids (humic acid, tartaric acid, citric acid), cationic heavy metals (represented by Pb(II) and Cd(II)), simulated anionic heavy metals (represented by PO4 3- As a representative) as a coexisting component for adsorption experiments. Among them, cationic heavy metals have no effect on the adsorption process, and the maximum adsorption rate is still 100%. Low molecular weight organic acids have the greatest impact, but the maximum adsorption rate is still maintained at 84.04%. When all components exist together, the chitosan imprinted cross-linked material still has an adsorption rate of 83.04% for Cr(VI), which is within an acceptable range, indicating that the material has good selectivity for Cr(VI) and can effectively eliminate the influence of interfering components.

[0097] In summary, the present invention is extended from Cr in Example 1 to other heavy metals. The template ion Cr(VI) is added to the chitosan sol by mixing and stirring and is fully mixed so that the template ion is combined with the adsorption active site of chitosan. Then, the mixed sol is dropped into a cross-linking agent sodium tripolyphosphate solution by a sol-gel method to form chitosan imprinted cross-linked gel balls. Finally, the template ion is eluted to obtain a chitosan imprinted cross-linked material. The obtained material has the characteristics of simple preparation, environmental friendliness, low cost, easy availability, good adsorption performance, strong selectivity, in-situ detoxification and enrichment, etc.

Claims

1. A method for preparing a chitosan imprinted cross-linked material for selective adsorption of heavy metals in water, characterized in that: The following steps are involved: Step 1, preparing heavy metal imprinted chitosan sol: at room temperature, adding chitosan powder to a diluted glacial acetic acid solution to obtain a mixed sol, adding template ions to the mixed sol, and mixing them evenly to obtain a heavy metal imprinted chitosan sol; in terms of mass ratio, chitosan powder: glacial acetic acid solution: template ions = (1.00-2.00): (50.17-100.34): (10.04-20.08); the mass percentage concentration of the glacial acetic acid solution is 1.58-3.05%; Step 2, preparing heavy metal imprinted chitosan cross-linked gel spheres: under normal temperature conditions, dripping the heavy metal imprinted chitosan sol prepared in step 1 into the sodium tripolyphosphate solution drop by drop at a uniform speed to form heavy metal imprinted chitosan cross-linked gel spheres of uniform size; in terms of mass ratio, heavy metal imprinted chitosan sol: sodium tripolyphosphate solution = (1.00-2.00): (250.53-501.05); the mass percentage concentration of the sodium tripolyphosphate solution is 0.50-1.00%; Step 3, heavy metal imprinted chitosan cross-linked gel ball template ion elution: add the heavy metal imprinted chitosan cross-linked gel ball prepared in step 2 into the eluent and shake, then separate the heavy metal imprinted chitosan cross-linked gel ball, add the eluent and centrifuge, then place the heavy metal imprinted chitosan cross-linked gel ball in the eluent neutralizer and centrifuge, then dry under freezing conditions to obtain a chitosan imprinted cross-linked material for heavy metal selective adsorption; by mass ratio, heavy metal imprinted chitosan cross-linked gel ball: eluent = (1.00-2.00): (1170.29-2340.58); eluent: eluent neutralizer = (1170.29-2340.58): (179.80-359.60); the structural formula of the chitosan imprinted cross-linked material is: Among them, m / (m+n)≥95%; The template ion is one of Cr, Mo, W or As; The eluent is a sodium hydroxide solution; the mass percentage concentration of the sodium hydroxide solution is 3.67-7.34%; The eluent neutralizer is a nitric acid solution; the mass percentage concentration of the nitric acid solution is 0.019-0.043%.

2. The chitosan imprinted cross-linked material obtained by the preparation method according to claim 1, characterized in that: Its structural formula is: Among them, m / (m+n)≥95%.

3. The use of the chitosan imprinted cross-linked material obtained by the preparation method according to claim 1, characterized in that: Used in the purification of wastewater containing heavy metals.